2012
DOI: 10.3109/14017431.2012.673728
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the diagnoses atrial fibrillation and atrial flutter in a Danish patient registry

Abstract: This study shows that the validity of the diagnosis of AF and/or AFL is high and may be used for registry-based studies. A specified diagnosis of AFL was rarely used and was not reliable to distinguish between cases of AF and AFL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(136 citation statements)
references
References 17 publications
4
132
0
Order By: Relevance
“…The AF diagnosis has been shown to be accurate in Danish registries. 29 However, we were not able to distinguish between new-onset AF from carry-over diagnosis in relation to another condition (or 30 For the HF diagnosis, a validation study involving a single Danish hospital showed this diagnosis to be specific (99% specificity) but under-reported (29% sensitivity) 16 ; the extent to which these findings generalize to all hospitals in Denmark is unclear. In all, we cannot completely rule out misdiagnosis of HF nor underdiagnosis of AF (silent or asymptomatic).…”
Section: Limitationsmentioning
confidence: 87%
“…The AF diagnosis has been shown to be accurate in Danish registries. 29 However, we were not able to distinguish between new-onset AF from carry-over diagnosis in relation to another condition (or 30 For the HF diagnosis, a validation study involving a single Danish hospital showed this diagnosis to be specific (99% specificity) but under-reported (29% sensitivity) 16 ; the extent to which these findings generalize to all hospitals in Denmark is unclear. In all, we cannot completely rule out misdiagnosis of HF nor underdiagnosis of AF (silent or asymptomatic).…”
Section: Limitationsmentioning
confidence: 87%
“…Some clinicians may confuse the diagnoses of AF and AFL, 36 reducing the validity of diagnostic coding for AFL. 37 This could potentially account for the differences in AF and AFL risk by race. Although our results are in agreement with previous investigations performed in well-characterized cohort studies (albeit limited to white and black patients) demonstrating a reduced risk of AF among blacks, it remains possible that blacks, Hispanics, and Asians more frequently seek hospital-based care for non-AF diagnoses compared with whites.…”
Section: Discussionmentioning
confidence: 99%
“…We relied on hospital diagnoses to identify patients with atrial fibrillation, but the validity of this register-based diagnosis is high. 22 Similarly, the positive predictive value of a first diagnosis of diabetes mellitus is high (>95%). 23 We restricted our follow-up period to 5 years, as duration of diabetes mellitus inherently increases during follow-up.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…22 Incident cases of atrial fibrillation not habitually residing in Denmark were excluded, as were patients with a previous diagnosis of cancer and patients who died or were diagnosed with thromboembolism or transient ischemic attack on the day of admission ( Figure 1). …”
Section: Study Populationmentioning
confidence: 99%